Thermal Conductivity of Sodium Silicate Glasses and Melts: Contribution of Diffusive and Propagative Vibration Modes - Sukenaga, Sohei; Endo, Takahiko; Nishi, Tsuyoshi; Yamada, Hiroki; Ohara, Koji; Wakihara, Toru; Inoue, Koji; Kawanishi, Sakiko; Ohta, Hiromichi; Shibata, Hiroyuki (Frontiers in Materials, 2021)
The thermal conductivity of silicate melts and glasses is an important physical property for understanding the temperature distribution in high-temperature metallurgical processes; however, the mechanism of heat conduction in these non-crystalline materials remains unclear. Two types of vibration modes must be considered to understand the mechanism of heat conduction, namely, propagative and diffusive vibration modes. In the present study, we carefully derived the thermal conductivity of pure silica and sodium disilicate glasses and melts, and estimated the contribution of the diffusive vibration mode using a recently developed model. The results indicated that the diffusive vibration mode was not dominant in the silicate non-crystalline materials, whereas the propagative vibration mode (i.e., phonons) was dominant in the heat conduction of silicate glasses and melts, which is in contrast with borate glasses.